Analysis of the Dieng Culture Festival from the Perspective of Sustainable Tourism - Haryanto, Agus; Reigita Shandy, Ivonia; Allen Setyawan, Queenna (KnE Social Sciences, 2023)
Dieng Culture Festival is a tourist activity in Dieng, Central Java, which has become an international tourism event where visitors come from local and foreign tourists. This paper tries to elaborate on how to implement the Dieng Culture Festival from a sustainable tourism perspective. For this reason, the research that forms the basis of this paper seeks to analyze descriptively the implementation of the Dieng Culture Festival. Then, the author collects data in the form of documents and interviews and then the author analyzes the data with a sustainable tourism perspective. This study found that the implementation of the Dieng Culture Festival has fulfilled two elements of sustainable tourism, namely from the economic, and social and cultural aspects. However, this study found that the Dieng Culture Festival has not fulfilled environmental aspects. Keywords: Dieng Culture Festival, sustainable tourism, Indonesia